The apocalypse - Jones, Justin; Latt, David Michael; de los Rios, Carlos; Faith Films; Echo Bridge Home Entertainment; Viva Video ([United States] [Distributed by] Echo Bridge Home Entertainment ; distributed in the Philippines by Viva Video, 2010)
In this epic film of faith, a mother and father search for their only child as a giant asteroid headed for Earth triggers a series of apocalyptic events.
Originally released as a motion picture in 2007.
Cinematography, Adam Silver ; editor, Kristen Quintrall.
MPAA rating: Not rated.
VCD
Keywords: End of the world -- Drama; Families -- Drama; Asteroids -- Collisions with Earth -- Drama; Asteroids -- Collisions with Earth; End of the world; Families